Programmable Helicity and Spin Polarization in Pt6L4 Coordination Capsules through Guest-Mediated Chiral Control - Zhong Wei; Xu Jing; Junkai Cai; Zhixin Wang; Guowei Geng; Song Zhao; Chunying Duan (Journal of the American Chemical Society, 2026)
Abstract Programmable regulation of spin polarization enables molecular-scale spin filtering, yet reversible control of its sign in supramolecular systems remains challenging. Herein, a chiral-directing strategy modulates multiple helical states of octahedral capsules, enabling programmable and reversible control of chirality-induced spin selectivity (CISS). The strategy transfers (R)-1,1′-bi-2-naphthol chirality to induce capsule helicity, followed by controlled helicity inversion upon introduction of (R)-1,1′-binaphthyl-2,2′-diylhydrogen phosphate via host–guest interactions. Magnetic circular dichroism (MCD) reveals chirality-dependent changes in electronic states, while magnetic conductive atomic force microscopy (mc-AFM) independently demonstrates spin-selective charge transport. Systematic modulation of host–guest electronic coupling enables reversible switching of spin polarization. These results demonstrate that dynamic, chirality-matched host–guest interactions emulate enzymatic stereochemical control, offering molecular-level insight and a general design principle for chiral coordination architectures with programmable spin functions.